A Multi-Tissue, Multi-Species Assessment of Lipid and Urea Stable Isotope Biases in Mesopredator Elasmobranchs - Bennett-Williams, Joshua; Skinner, Christina; Wyatt, Alex S. J.; McGill, Rona A. R.; Willis, Trevor J. (Frontiers in Marine Science, 2022)
The application of stable isotope analysis (SIA) is increasing in elasmobranch trophic ecology, but inconsistency remains in terms of the tissue pre-treatment methods chosen to remove biases introduced by lipids and urea. SIA of a range of non-lethally extracted tissues from a diverse group of elasmobranchs, including mesopredators, is increasing, yet most studies assume that isotope biases from lipid and urea are the same across tissues and species. To determine tissue- and species-specific isotope biases across treatment methods, three tissues and their components [muscle, fin, and blood separated into plasma and red blood cells (RBC)] were non-lethally extracted from three species of mesopredatory elasmobranchs and subjected to one of three treatment methods: (1) deionized water rinse [DW], (2) chloroform/methanol lipid extraction [LE], or (3) deionized water followed by chloroform/methanol [DW+LE]. In muscle δ13C, all treatments displayed minimal variation (∼ 0‰) but large increases in δ15N (∼ 1‰) indicated urea removal. Fin δ13C values decreased with DW but increased with LE and DW+LE, whilst all treatments increased fin δ15N (∼ 0.5‰), suggesting removal of both lipid and urea. Plasma δ13C and δ15N displayed high individual variation; large decreases in δ13C (∼−0.8‰) across all treatments, but particularly DW, suggested the removal of 13C-enriched compounds while a small increase in δ15N (∼ 0.2‰) suggested minimal urea removal. In RBC, all treatments showed small δ13C declines (∼−0.5‰), with no difference in δ15N, suggesting minimal removal of 13C-enriched compounds and urea. For muscle and fin, DW+LE is the most appropriate treatment to standardize δ13C and δ15N consistently across individuals and tissues. The large individual variation in treatment effects on plasma suggests it is unsuitable for current treatment methods. Consistent treatment effects for RBC allow for DW+LE standardization, however, broader species-specific effects are unknown. The importance of treatment choice for accurately estimating prey contributions to elasmobranch diet was highlighted using Bayesian stable isotope mixing model comparisons, with prey contributions varying significantly among treatments. This variability suggests that ecological inferences from elasmobranch tissue SIA are not robust to different treatment methods. It is recommended that studies employ standardized corrections using a combined DW+LE treatment where applicable.